2020
DOI: 10.1007/s11695-020-04763-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prediction Models for Type 2 Diabetes Relapse After Post-bariatric Surgery Remission: a Post hoc Analysis of 15-Year Follow-up Data from the Swedish Obese Subjects (SOS) Study

Abstract: Purpose Many patients achieve type 2 diabetes (T2D) remission after bariatric surgery, but relapse after post-surgery remission is common. Scoring models accurately predict remission up to 5 years after surgery but have not been tested for prediction of longterm T2D relapse. The aim of this work was to test the ability of prediction models and single predictors to identify patients at risk of long-term relapse (10-15 years) after post-surgery T2D remission. Methods We identified 222 individuals with T2D from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For example, a recent US study found that 35% of those who had remission of diabetes after bariatric surgery had recurrence within 5 years, 1 and recently published data from the Swedish Obese Subjects study showed overall relapse rate of 54% at 10 years. 8 Risk factors for diabetes relapse after surgery include a longer duration of diabetes, preoperative insulin use, poor preoperative glycemic control, impaired β-cell function, greater preoperative weight and a lesser degree of postoperative weight loss. [1][2][3] However, even if diabetes relapses it often requires less medication 3 9 10 and a recent study…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent US study found that 35% of those who had remission of diabetes after bariatric surgery had recurrence within 5 years, 1 and recently published data from the Swedish Obese Subjects study showed overall relapse rate of 54% at 10 years. 8 Risk factors for diabetes relapse after surgery include a longer duration of diabetes, preoperative insulin use, poor preoperative glycemic control, impaired β-cell function, greater preoperative weight and a lesser degree of postoperative weight loss. [1][2][3] However, even if diabetes relapses it often requires less medication 3 9 10 and a recent study…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study has shown low predictive performance of these models, and their use in clinical practice has been limited. 8 More data and a better understanding of diabetes trajectory following bariatric surgery are needed to identify those at highest risk of diabetes relapse and to allow for appropriate monitoring and timely institution of treatment. We have also analyzed data among those with pre-existing T2D who underwent surgery, to better understand the rates, time course and factors associated with remission and relapse.…”
mentioning
confidence: 99%
“…[11,12] Many patients achieve T2DM remission after bariatric surgery, whereas some patients experience T2DM recur-rence years after surgery. [13,14] The effect of bariatric surgery on T2DM control can be assessed based on predictive models of T2DM remission. Currently, there are more than 10 models for predicting T2DM remission and those models are divided into two categories: scoring and logistic regression systems.…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery is the most effective treatment for severe obesity [ 1 ]. Roux-en-Y Gastric Bypass (RYGB) is a widely performed bariatric surgery procedure with a very favourable benefit-to-risk ratio.…”
Section: Introductionmentioning
confidence: 99%